Breastfeeding Benefits and Resources: What is a galactagogue? - Diana Hazard Taft (EDIS)
A galactagogue is a food, herb, or medication that helps increase the production of breastmilk. This publication provides some basic information about galactagogues for anyone interested in the topic.